Frequency of Non-motor Symptoms in Parkinson's Patients With Motor Fluctuations - Fernandes, Mariana; Pierantozzi, Mariangela; Stefani, Alessandro; Cattaneo, Carlo; Bonizzoni, Erminio A.; Cerroni, Rocco; Mercuri, Nicola Biagio; Liguori, Claudio (Frontiers in Neurology, 2021)
Background: Non-motor symptoms (NMS) including neuropsychiatric, sleep, autonomic, and sensory domains are an integral aspect of the clinical presentation of Parkinson disease (PD) and affect neurocognitive functioning as well as patients’ and caregivers’ well-being. Objective: To describe the occurrence of NMS in PD patients with motor fluctuations in real-life condition. Methods: The present study is a secondary analysis of a previous multinational, multicenter, retrospective-prospective cohort observational study (SYNAPSES). Patients with PD diagnosis and motor fluctuations aged ≥18 years were included. Data achieved at the baseline visit were used for this study and descriptive analyses were conducted to describe the distribution of NMS in motor-fluctuating PD patients distributed according to different clinical characteristics. Results: Of the 1610 patients enrolled, 1589 were included for the analysis (978 Males and 611 Females), with a mean age of 68.4 (SD=9.6). Most patients had at least one NMS (88.5%). Sleep problems and psychiatric symptoms were the most prevalent NMS in motor fluctuating PD patients in all H&Y stages. Psychiatric disorders were more frequent in older patients and in patients with a larger number of years of PD diagnosis, while sleep problems were more preeminent in younger patients and with inferior disease duration. Conclusions: The present findings further support the high prevalence of NMS in PD patients with motor fluctuations, reinforcing thus the need for assessing them for diagnostic accuracy and for delivering holistic care.